2016
DOI: 10.4172/2165-7548.1000338
|View full text |Cite
|
Sign up to set email alerts
|

Acute Psychiatric Problems among Migrants Living in Switzerland- a Retrospective Study from a Swiss University Emergency Department

Abstract: Background: Switzerland is a traditional immigration country with immigrants from both neighbouring, and less developed countries. Since the early 1990s, the migration rate has continuously increased and in 2013 almost a quarter of Swiss residents had an immigration background. Immigrants in Switzerland had fewer psychiatric hospitalisations, but more emergency and compulsory admissions than the local population. Therefore it is important to study the characteristics of the immigrant population presenting at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In the same period, the number of psychiatric cases in the native population increased by 17.8%. Similar findings have been seen in other studies on psychiatric problems among immigrants in ED [ 9 , 30 ]. As a comparison, other Swiss studies have found increasing numbers of psychiatric patients in ED (from 60 to 315 per year between 2007 and 2012) and the most common reasons for psychiatric presentation to ED were psychosis (20.3%), social problems (18.2%), auto-aggression (16.4%), and depression (16.2%) [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the same period, the number of psychiatric cases in the native population increased by 17.8%. Similar findings have been seen in other studies on psychiatric problems among immigrants in ED [ 9 , 30 ]. As a comparison, other Swiss studies have found increasing numbers of psychiatric patients in ED (from 60 to 315 per year between 2007 and 2012) and the most common reasons for psychiatric presentation to ED were psychosis (20.3%), social problems (18.2%), auto-aggression (16.4%), and depression (16.2%) [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, there are gaps in current knowledge in this research area. A few publications have explored differences between immigrants and nationals [ 6 , 7 , 8 , 9 , 10 , 11 ], socioeconomic status [ 6 ], or general well-being and health of short- and long-term immigrants [ 7 , 12 , 13 , 14 ]. Some studies have found that immigrants attend EDs more often than host populations—but these findings have not been consistent [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established by Chatzidiakou et al (2016) that the traumatic experiences that refugees undergo during migration may lead to them to develop psychosocial issues in the new country of destination. They highlight the acute psychiatric health problems experienced by migrants living in Switzerland [21].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, major challenges such as cultural and language barriers need to be addressed [ 7 , 13 ]. Utilization patterns among immigrants in general have already been assessed in the Swiss context [ 14 , 15 , 16 ]. Nevertheless, data for asylum seekers are particularly scarce.…”
Section: Introductionmentioning
confidence: 99%